Gender Education in the Context of Husband's Involvement in the Sphere Domestic: An Interdisciplinary Study of Islamic Family Law and Studies Gender - Akhmad Abdul Mujib Mujib; Muhammad Syakur; M. Jamal; Muh. Baehaqi; Sumarjoko; Husna Nashihin (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
This study aims to determine: (1) the division of roles in carrying out household chores (2) the division of roles in raising children. This study uses a qualitative method. Data sources were selected using purposive sampling, with six informants consisting of three families. Data were collected using observation, interview and documentation techniques. Analysis of the research results used data reduction steps, data presentation and data verification. The results of the study show that: (1) the division of roles in household work is divided into two, namely household work that is done together and household work that is done individually. Household work that is done together and individually such as cooking, washing clothes and cleaning the house. (2) division of roles in raising children. The division of roles in raising children is also divided into two, namely, child care that is done together and child care that is done individually. The division of roles in raising children includes taking and picking up children from school, helping children with homework, and teaching children to recite the Koran. The division of domestic roles in each farming family is different, this depends on the habits and agreements made between husband and wife.